Staff performance in call service recovery in Thailand's insurance industry - NIYOMDECHAR, R.; SYAMALAKUMARI, P. V. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This study investigates the mediating effect of surface traits, Individual Customer Orientation (ICO), towards the relationship between Internal Service Quality (ISQ) and Service Recovery Performance (SRP) in the call center. Using Service Profit Chain (SPC), the integral part of internal service quality was proposed through organizational factors, work environment, and personal factors (modeled as backgrounds).  Self-administered questionnaires were distributed to 858 call center employees who worked in insurance companies. The results revealed that frontline employees’ individual customer orientation mediates the relationship between internal service quality and service recovery performance. RESUMEN Este estudio investiga el efecto mediador de los rasgos superficiales, la Orientación Individual al Cliente (ICO) hacia la relación entre la Calidad del Servicio Interno (ISQ) y el Desempeño de Recuperación del Servicio (SRP) en el centro de llamadas. Utilizando Service Profit Chain (SPC), se propuso la parte integral de la calidad del servicio interno a través de factores organizacionales, del entorno laboral y factores personales (modelados como antecedentes). Se distribuyeron cuestionarios autoadministrados a 858 empleados del centro de llamadas que trabajaban en compañías de seguros. Los resultados revelaron que la orientación individual al cliente de los empleados de primera línea media la relación entre la calidad del servicio interno y el desempeño de recuperación del servicio.